Proton pump inhibitors are associated with lower gastrointestinal tract bleeding in low-dose aspirin users with ischaemic heart disease. Issue 9 (September 2015) - Miyake, Kazumasa; Akimoto, Teppei; Hanada, Yuriko; Nagoya, Hiroyuki; Kodaka, Yasuhiro; Ueki, Nobue; Kusunoki, Masafumi; Kawagoe, Tetsuro; Futagami, Seiji; Takahashi, Yasuhiro; Takano, Hitoshi; Sakamoto, Choitsu
Abstract Background Impact of acid suppressants on lower gastrointestinal bleeding remains unclear in low-dose aspirin users; we aimed to investigate this relationship. Methods Retrospective cohort study of low-dose aspirin users who underwent coronary angiography for ischaemic heart disease in our institution between October 2005 and December 2006; patients were evaluated for upper or lower gastrointestinal bleedings within 3 years post-angiography. Results 538 patients were enrolled (males, 74.4%; mean age 67.4 ± 10.6 years). Risk for upper gastrointestinal bleeding decreased with concomitant use of statins (HR, 0.37; 95% CI, 0.15–0.89), calcium channel blockers (HR, 0.29; 95% CI, 0.10–0.85), and histamine-2 receptor antagonists (HR, 0.26; 95% CI, 0.08–0.89). Concomitant use of proton pump inhibitors tended to decrease risk of upper gastrointestinal bleeding (HR, 0.27; 95% CI, 0.06–1.18). Risk for lower gastrointestinal bleeding increased with both concomitant use of warfarin (HR, 15.68; 95% CI, 4.43–55.53) and proton pump inhibitors (HR, 6.55; 95% CI, 2.01–21.32), but not with histamine-2 receptor antagonists. Hyperuricemia lowered risk for lower gastrointestinal bleeding (HR, 0.12; 95% CI, 0.02–0.88). Conclusions In low-dose aspirin users, concomitant use of proton pump inhibitors increased lower gastrointestinal bleeding risk, independent from effects on upper gastrointestinal bleeding.